Statistical inference in school - Szász-Simon, Judit (Teaching Mathematics and Computer Science, 2004)
The paper explains a classroom example for convincing students about the utility and applicability of statistical methods in learning getting people’s opinions. The emphasis is on convincing instead of proving. The necessary statistical data may be obtained from the Internet as a digital text.